RELATIONSHIP BETWEEN PUERPERAL GYMNASTICS WITH THE SMOOTH ELIMINATION IN MATERNAL POSTPARTUM - Novita Nurhidayati; Triani Yuliastanti (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2013)
Background puerperal period lasted for approximately 6 weeks or 40 days, with a variety of complaints not only physical problems but also associated with psychosocial problems such as anxiety, impaired body image and acceptance. During the postpartum period saw various inconveniences such us difficulties include the elimination defecation and urination. Most of the new mothers cannot defecate for 3 days to 5 days after birth this was due to fear and the abdomen anal muscles stretch. The discomfort can be overcome with postnatal exercise. Research purposes this study aims to determine the relationship between puerperal gymnastics with the smooth elimination in maternal postpartum. Research method research conducted using survey methods of analytic and cross sectional approach. This study population is all postnatal mothers to 1-6 in know led of private midwives (BPS) Prima Mudal on April to June 2013 with a total sampling and data analysis chi square. Result the calculation of chi square with  0, 05, p value (0, 0001<0, 05), it mean Ha be accepted and Ho rejected. Conclude of this study it can be concluded that there is a relationship between puerperal gymnastics with the smooth elimination in maternal postpartum.